Treating posttraumatic stress disorder remotely with cognitive therapy for PTSD. Issue 1 (14th July 2020) - Wild, Jennifer; Warnock-Parkes, Emma; Murray, Hannah; Kerr, Alice; Thew, Graham; Grey, Nick; Clark, David M.; Ehlers, Anke
ABSTRACT: Delivering trauma-focused cognitive behavioural therapy to patients with PTSD during the COVID-19 pandemic poses challenges. The therapist cannot meet with the patient in person to guide them through trauma-focused work and other treatment components, and patients are restricted in carrying out treatment-related activities and behavioural experiments that involve contact with other people. Whilst online trauma-focused CBT treatments for PTSD have been developed, which overcome some of these barriers in that they can be delivered remotely, they are not yet routinely available in clinical services in countries, such as the UK. Cognitive therapy for PTSD (CT-PTSD) is a trauma-focused cognitive behavioural therapy that is acceptable to patients, leads to high rates of recovery and is recommended as a first-line treatment for the disorder by international clinical practice guidelines. Here we describe how to deliver CT-PTSD remotely so that patients presenting with PTSD during the COVID-19 pandemic can still benefit from this evidence-based treatment.